Retrospective Study of Energy Requirement Recommendations for Dogs in a Brazilian Veterinary Hospital (2013–2025) - Pedro Henrique Marchi; Leonardo de Andrade Príncipe; Gabriela Luiza Fagundes Finardi; Natália Manuela Cardoso de Oliveira; Gabriela Pinheiro Tirado Moreno; Maria Carolina Farah Pappalardo; Felipe Sesti Trindade; Júlio Cesar de Carvalho Balieiro; Thiago Henrique Annibale Vendramini (Animals)
Accurate estimation of metabolizable energy requirements (MER) is essential for appropriate dietary planning in dogs. However, standardized recommendations may not reflect the variability observed in clinical practice, particularly regarding individual factors such as neutering status, body condition, and age. This study aimed to retrospectively assess the MER factor in dogs treated at a Brazilian veterinary hospital, considering variables including sex, neuter status, body condition score (BCS), muscle mass score (MMS), body size, and life stage, and to compare the findings with those typically reported in the scientific literature. A total of 438 medical records from 2013 to 2025 were reviewed for this study. Data on demographic and clinical variables were collected, and MER factors were calculated based on energy intake and body weight. Statistical analyses were conducted to evaluate the interactions between variables, particularly BCS and neutering status. The study population included 253 males (57.8%) and 185 females (42.2%), with 80.6% of them being neutered. The MER values varied widely across the subgroups. Neutered dogs had consistently lower energy factors than intact dogs (p < 0.0001), and energy requirements decreased progressively with increasing BCS, regardless of neutering status (p < 0.05). A significant interaction between BCS and neutering status was observed (p = 0.0089), although BCS alone was not a significant predictor (p = 0.9670). No substantial differences were observed based on sex, body size, or life stage. MER values observed in clinical practice differ from standard recommendations and are influenced by the interaction between neutering status and body condition. These findings reinforce the need for individualized nutritional assessments in companion animal medicine and call for further studies to refine clinical energy estimation models.